Pengaruh Model Penerimaan Teknologi terhadap Loyalitas Penggunaan Mobile Banking oleh Nasabah Bank Syariah di Kota Bandung - Bahmid I Magi; Asep Abdul Halim; Setiawan Setiawan (Masoem University, 2023)
This research was conducted to determine the effect of Islamic bank customer loyalty which is influenced by the technology acceptance model which is proxied by perceived ease of use and perceived usefulness. Data obtained from customers of Islamic banks in the city of Bandung as many as 168 respondents using a questionnaire. Dayang data analysis used was SEM-PLS. the results of the study show that perceived ease of use has a significant positive effect on customer loyalty. In addition, perceived usefulness has a significant positive effect on customer loyalty. The results of this study are expected to trigger Islamic banks to further improve mobile banking facilities so that customers can continue to use Islamic bank mobile banking technology.